Diagnostic Laparoscopy Versus Routine Exploratory Laparotomy in Hemodynamically Stable Abdominal Trauma: A Systematic Review and Meta-Analysis of Non-Therapeutic Intervention Rates and Clinical Outcomes - Tito Pradipta; Amriansyah Pranowo (HM Publisher, 2025)
Background: Exploratory laparotomy (EL) has traditionally been the standard for evaluating significant abdominal trauma, but it carries a high rate of non-therapeutic procedures and associated morbidity. Diagnostic laparoscopy (DL) has emerged as a minimally invasive alternative, though its precise benefits remain to be quantified by a comprehensive meta-analysis of recent evidence. This study aims to compare the rates of non-therapeutic laparotomy and key clinical outcomes between DL and EL in the management of hemodynamically stable patients with abdominal trauma. Methods: Following PRISMA guidelines, a systematic search of PubMed, Scopus, Web of Science, and the Cochrane Library was conducted for studies published between January 2015 and February 2025. We included comparative studies (randomized controlled trials and observational studies) evaluating DL versus EL in adult, hemodynamically stable patients with blunt or penetrating abdominal trauma. The primary outcome was the rate of non-therapeutic laparotomy. Secondary outcomes included overall postoperative morbidity, surgical site infection (SSI) rates, length of hospital stay (LOS), and mortality. A random-effects model was used for meta-analysis to calculate pooled Odds Ratios (OR) and Mean Differences (MD) with 95% Confidence Intervals (CI). Results: Eight studies involving 1,550 patients (775 in the DL group, 775 in the EL group) were included. The DL group had a significantly lower rate of non-therapeutic laparotomy compared to the EL group (11.5% vs. 38.8%; pooled OR 0.18, 95% CI [0.10, 0.31], p<0.00001; I2=45%). Furthermore, DL was associated with a significant reduction in overall morbidity (OR 0.45, 95% CI [0.34, 0.60], p<0.00001; I2=22%) and SSI rates (OR 0.38, 95% CI [0.24, 0.61], p<0.0001; I2=0%). The mean LOS was shorter in the DL group by 3.15 days (MD -3.15, 95% CI [-3.88, -2.42], p<0.00001; I2=78%). There was no significant difference in mortality rates between the two groups (OR 0.85, 95% CI [0.45, 1.62], p=0.62; I2=0%). Conclusion: In hemodynamically stable patients with abdominal trauma, a selective strategy involving diagnostic laparoscopy drastically reduces the likelihood of non-therapeutic surgical intervention. This approach is also associated with significantly lower postoperative morbidity, fewer surgical site infections, and a shorter hospital stay without compromising patient survival. These findings strongly support the integration of diagnostic laparoscopy as a primary diagnostic and therapeutic tool in modern trauma management algorithms.